Optimal Control Problem of Food Intake of Swine During Post Weaning Period - Kiataramkul, Chanakarn; Matkhao, Puttida (Agriculture and Natural Resources, 2015)
The amount of food intake clearly affects swine body weight. The most suitable weight of swine on the day of sale is the weight that fetches the best price. The objective of this research was to minimize the amount of food fed to swine in the post weaning period so that the weight reaches a desirable final value on a fixed day of sale. Optimal control problems were derived by assuming that the weight increase follows either the logistic or the Gompertz equations with parameters estimated from actual growth data. Numerical solutions of the optimal control problem were obtained and discussed.